A new genus and six new species of the tropical Camptotypus genus-group (Hymenoptera: Ichneumonidae; Pimplinae) from northern South America - Sääksjärvi, Ilari E.; Palacio, Edgard; Gauld, Ian D.; Jussila, Reijo; Salo, Jukka (Zootaxa, 2003)
The new northern South American genus Amazopimpla gen.n. and six new species (Amazopimpla errabunda sp.n. from Peru; Amazopimpla farallonensis sp.n. from Colombia; Amazopimpla guayanaensis sp.n. from Guayana; Amazopimpla lutea sp.n. from Colombia; Amazopimpla matogrossoensis sp.n. from Brazil and Amazopimpla taunoi sp.n. from Colombia and Peru) are described. An identification key and illustrations are provided as well as a short discussion of the species richness and distribution area of the genus.